The Impact of Work-Life Conflict on Employees’ Emotional Wellbeing and the adoption of Quiet Quitting in the Hospitality Industry - Rocha, Helena Carina Ferreira da (2024)
In a fast-changing, increasingly dynamic, and competitive work world, organizations seek to differentiate themselves and employees expect more and more in what concerns to their well-being. In addition to assure a healthy organizational climate, the respect for the necessary balance between individuals' personal and professional lives is becoming increasingly important. These challenges become more noticeable in the hospitality industry: the workload, shift work, rotating days off, among other peculiarities, have a negative impact on the personal lives of the human capital in this industry, who find it difficult to find a satisfactory work-life balance, despite having a high burnout rate. The Covid-19 pandemic has highlighted this importance and instilled in individuals a new sense of priority when it comes to negotiating leisure and work time. In this context, new work phenomena have emerged, such as quiet quitting, characterized by the adoption of passive behaviors aimed only at fulfilling the tasks that are strictly necessary and inherent to the job. This study aims to understand the impact of work-life conflict on the emotional well-being of employees in the Portuguese hotel sector and on their adoption of quiet quitting. To accomplish this, a quantitative method was applied, using questionnaires to survey employees of 4 and 5-star hotels in the Porto and Northern region of Portugal. Once the data had been collected, with 175 answers, it was analyzed using SPSS and statistically significant relationships were investigated using Spearman correlations and linear regressions. It was possible to verify the existence of statistically significant positive correlations between work-life conflict and work-leisure conflict with the negative dimension of emotional well-being (negative affect), both negative dimensions of burnout (emotional exhaustion and depersonalization) and with quiet quitting intentions. There was also a statistically significant positive relationship between the negative dimensions of burnout and quiet quitting intentions and between the negative dimension of well-being and quiet quitting.